“COLOR AND FORM IN SAMARKAND ARCHITECTURE: BALANCING HISTORICAL AND MODERN URBAN DESIGN” - Nuriddinova Diyora Jasurbek Qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores how color and form in Samarkand’s architecture contribute to balancing historical heritage with modern urban design. The study examines iconic historical sites such as Registan Square, Shah-i-Zinda, and Gure Amir Mausoleum alongside contemporary buildings and public spaces. The research emphasizes strategies to maintain visual harmony, aesthetic continuity, and cultural identity while accommodating modern urban development.